Backward-oriented economics - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Nowadays, academic journals of high standing rarely accept a conceptual idea in a paper not instantly accompanied by econometric estimates. The idea would almost certainly get rejected. Empirical validation based on past statistical data has produced an unfortunate backward orientation in economics. While one can learn from the past, this approach fails when the underlying conditions strongly change. The paper suggests various possibilities to overcome the intense publication pressure in so-called top journals and the overemphasis on instant empirical evidence. Academia is, however, unlikely to adapt. As economics is too backward oriented, other disciplines or cranks may well dominate future economic policy.
Keywords: A10; A11; B40; C10; C80; 330